Obtenção e avaliação de pó de osso liofilizado bovino para uso em impressão tridimensional - Fávero, Giovani (2016)
The development of raw material (MP) atypical for use in Rapid Prototyping equipment (PR) which have 3DP printing technology has expanded the application areas such equipment. Lyophilized bovine bone (OLB), atypical MP proposed in this study is found in various formats and options of brands available for use in medicine, dentistry and veterinary medicine, as bone implants and grafts. Based on this scenario, this study aimed to process rectangular block OLB by developing a methodology and construction equipment adapted for the comminution of the blocks. This methodology proved to be efficient in processing blocks OLB fine powder and allowed replication of the comminution process developed for the study. Still, it was carried out the characterization of virgin powder ZP 131® and OLB fine powder by scanning electron microscopy technique (SEM), X-Ray Spectroscopy Energy Dispersion (EDS) and particle size analysis. The average grain size curves for the tested powders used the Spline interpolation technique Cúbica of Akima, resulting convergence between the curves of the powders analyzed. The post had similar characteristics, meeting the minimum requirement print resolution of 3DP equipment. The statistical analysis applied to the powders revealed that the OLB fine powder showed less dispersion in relation to the other powdered and reached appropriate parameters for usein printing 3DP.